Rôle de la mare dans la gestion des systèmes pastoraux sahéliens du Ferlo (Sénégal) - Oumar Sy (Cybergeo, 2009)
The Ferlo is a region where the water problem is acute. The ponds are however many and varied. From the beginning until the end of the rainy season, they are frequented by the population, and contribute in the structuring of pastoral movements. But changes in their ability to accumulate water or in water quality become increasingly noteworthy. After disengaging from the management of drilling, governmental authorities have initiated the management of some of the ponds to reduce the water deficit in the region.